Gold removal from e-waste using high-intensity focused ultrasound - Axi Holmström; Topi Pudas; Jere Hyvönen; Martin Weber; Kenichiro Mizohata; Tom Sillanpää; Joni Mäkinen; Antti Kuronen; Tapio Kotiaho; Edward Hæggström; Ari Salmi (Ultrasonics Sonochemistry)
The demand for rare and precious metals (RPMs), e.g. gold, is increasing, as these are used in the ever-increasing amount of electronics needed for technological development and digitalization. Due to their rarity, virgin mining of RPMs is becoming more difficult and expensive. At the same time, over 62 Mt of e-waste is created globally each year. The high concentration of gold and other RPMs in e-waste makes it an excellent source for recycling. Unfortunately, current recycling methods need to separate the different metals and the current pyrometallurgical and hydrometallurgical processes also create toxic pollutants, large amounts of wastewater and require highly corrosive substances. Here we present a new method for gold removal for the purpose of recycling, using only water and high-intensity focused ultrasound to induce material erosion through cavitation. An 11.8 MHz ultrasonic transducer is used to first image the sample to locate gold-coated pads on discarded printed circuit boards (PCBs) and subsequently to remove only the gold layer. We demonstrate that the gold removal can be controlled by the number of transmitted ultrasonic bursts and that the energy efficiency is optimal when only minute amounts of the nickel layer beneath are also removed. Removing solely the gold layer also decreases the need for further processing steps. This greener gold removal method for e-waste is therefore well aligned with, and contributing to, the United Nations Sustainable Development Goal 12: Ensure sustainable consumption and production patterns.